Fraud Is What People Make of It: Election Fraud, Perceived Fraud, and Protesting in Nigeria. (October 2019) - Daxecker, Ursula; Di Salvatore, Jessica; Ruggeri, Andrea
Why do fraudulent elections encourage protesting? Scholars suggest that information about fraud shapes individuals' beliefs and propensity to protest. Yet these accounts neglect the complexity of opinion formation and have not been tested at the individual level. We distinguish between the mobilizing effects of actual incidents of election fraud and individuals' subjective perceptions of fraud. While rational updating models would imply that both measures similarly affect mobilization, we argue that subjective fraud perceptions are more consistent predictors of protesting, also being shaped by attitudes, information, and community networks. Our empirical analysis uses geo-referenced individual-level data on fraud events, fraud perception, and protesting from the 2007 Nigerian elections. Our analysis yields two main findings: proximity to reported fraud has no effect on protesting and citizens perceiving elections as fraudulent are consistently more likely to protest, and more so if embedded in community networks.